Prognostic role of HPV infection in esophageal squamous cell carcinoma - Laura Bognár; Ivett Hegedűs; Szabolcs Bellyei; Éva Pozsgai; László Zoltán; Katalin Gombos; Örs Péter Horváth; András Vereczkei; András Papp (Infectious Agents and Cancer, 2018)
Abstract Background The aims of this study were to evaluate whether HPV infection has a prognostic role in patients with esophageal squamous cell carcinoma who underwent oncological treatment and also to compare the heat shock proteins (Hsp) 90, 27 and 16.2 and growth hormone-releasing hormone receptor (GHRH-R) expression patterns of the pre-treatment tumor biopsies with the HPV status and with the oncological response. Methods Pre-treatment tumor biopsies of 74 patients with locally advanced esophageal squamous cell carcinoma were processed retrospectively. The presence of HPV was detected by chromogenic in situ hybridization. Hsp and GHRH-R expressions were determined using immunohistochemistry. Following neoadjuvant or definitive radiochemotherapy, the patients were restaged according to the Response Evaluation Criteria in Solid Tumors. The correlation between the HPV status, response to treatment and Hsp and GHRH-R expressions were evaluated. Results Fourteen (19%) patients were HPV-positive. These patients were more likely to respond poorly to multimodal therapy (71.4% were non-responders vs. 28.6% responders) and had shorter survival compared to HPV-negative patients (mean survival of 8 months vs. 11 months), although the difference was not significant. A significantly higher number of HPV-positive patients expressed Hsp 90 and 16.2 at high levels (93 and 79%, respectively) than at low levels (Chi-Square p = 0.019 and p = 0.031). Higher levels of Hsp expressions were associated with poorer response to therapy and worse overall survival. No correlation was found between GHRH-R expression and the HPV status, nor between GHRH-R expression and the treatment response of the examined samples. Conclusions We found that HPV infection was associated with poor response to oncological treatment and decreased overall survival, and therefore proved to be a negative prognostic factor in patients with esophageal squamous cell carcinoma. There was a linear correlation between levels of Hsp 90 and 16.2 expression and HPV positivity.